Advancing an Integrative Framework to Evaluate Sustainability in National Dietary Guidelines - Ahmed, Selena; Downs, Shauna; Fanzo, Jessica (Frontiers in Sustainable Food Systems, 2019)
The food system is responsible for some of society’s most pressing sustainability challenges. Dietary guidelines are one policy tool to help address the multiple sustainability challenges associated with food systems through dietary recommendations that better support environmental and human wellbeing. This article develops and applies a sustainability framework scoring tool comprised of four key dimensions (environmental, economic, human health, and sociocultural and political) and 32 sub-dimensions of sustainable food systems for the analysis and modification of national dietary guidelines. Two coders pilot tested the framework to quantify the occurrence of sustainability dimensions and sub-dimensions in national/regional dietary guidelines of 12 randomly selected high-income and upper-middle income countries including Albania, Australia, Brazil, the Grenadines, Grenada, Qatar, Netherlands, Nordic Countries, St. Vincent, Sweden, Thailand, the United Kingdom, and the United States. Sustainability Dimension Scores (SDS) were calculated as a percentage of the occurrence of the 8 sub-dimensions comprising each sustainability dimension and Total Sustainability Scores (TSS) were calculated as a percentage of the occurrence of the 32 sub-dimensions in each guideline. Inter-rater reliability of TSS and SDS indicated high validity of applying the sustainability framework for dietary guidelines. SDS varied between the four sustainability dimensions with human health being the most represented in the dietary guidelines examined, as hypothesized (average SDS score of 83%; range from 50-100%). Significant differences (p < 0.0001) were found in mean SDS between the four sustainability dimensions. Overall, results indicate that the ecological (average SDS score of 31%; range from 0-100%) economic (average SDS score of 29%; range from 0-100%), and socio-cultural and political (average SDS score of 44%; range of 0-100%) dimensions of sustainability are underrepresented in the examined national dietary guidelines with significant differences in SDS between guidelines (p < 0.0001). TSS varied by country between 12% to 74% with a mean score of 36% ( 20%). Brazil had the highest TSS (74%) followed by Australia (69%). The sustainability framework presented here can be applied by policy makers, researchers, and practitioners to identify gaps and opportunities to modify national dietary guidelines and associated programs for transforming food systems through diets that support planetary health.